2017
DOI: 10.3892/mmr.2017.7301
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA-222 in serum of patients with Alzheimer's disease

Abstract: The aim of the present study was to determine the association between Alzheimer's disease (AD) and microRNA‑222 in the serum of patients with AD. The expression of microRNAs was detected and the results were verified using microarray analysis and reverse transcription‑quantitative polymerase chain reaction. The results indicated that there were 35 strips of microRNA in the mild AD group, in which the difference of expression signal was >500 IU/ml. There were 26 strips of microRNA with a difference in expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Toward this goal, miR-21-5p and miR-322-5p (also identified as upregulated in exosomes from GSS infected cells, Bellingham et al, 2012 ), not previously suggested as biomarkers in blood serum/plasma of other NDs such as AD ( Geekiyanage et al, 2012 ; Kiko et al, 2013 ; Dong et al, 2015 ; Guo et al, 2017 ; Nagaraj et al, 2017 ; Zeng et al, 2017 ), MS ( Vistbakka et al, 2017 ), PD ( Ding et al, 2016 ; Dong et al, 2016 ; Ma et al, 2016 ), and ALS ( Freischmidt et al, 2013 ), emerge as prion-specific biomarker candidates. Other prion infected exosomal miRNAs with diagnostic potential include let-7b-5p, miR-29b-3p, miR-222-3p, and miR-342-3p; these miRNAs display inverse deregulation in prion infected exosomes (upregulation, Bellingham et al, 2012 ) compared to ALS (let-7b-5p in ALS patients serum, Freischmidt et al, 2013 ), or AD [miR-29b-ep in AD patients serum ( Geekiyanage et al, 2012 ) and/or PBMCs ( Villa et al, 2013 ), miR-222-3p in AD patients serum ( Zeng et al, 2017 ) and miR-342-3p in AD serum ( Tan et al, 2014 )]. Other upregulated in prion infected exosomes miRNAs, such as let-7i-5p and miR-128-3p, and the downregulated miR-146a-5p, display similar deregulation patterns in MS patients exosomes (let-7i-5p, Kimura et al, 2018 ), Primary Progressive (PPMS) MS patients serum (miR-128-3p, Vistbakka et al, 2017 ) and AD (miR-146a-5p, Kiko et al, 2013 ; Dong et al, 2015 ) or PD patients serum (miR-146a-5p, Ma et al, 2016 ).…”
Section: Altered Mirnas As Potential Diagnostic Tools In Prion Diseasmentioning
confidence: 99%
“…Toward this goal, miR-21-5p and miR-322-5p (also identified as upregulated in exosomes from GSS infected cells, Bellingham et al, 2012 ), not previously suggested as biomarkers in blood serum/plasma of other NDs such as AD ( Geekiyanage et al, 2012 ; Kiko et al, 2013 ; Dong et al, 2015 ; Guo et al, 2017 ; Nagaraj et al, 2017 ; Zeng et al, 2017 ), MS ( Vistbakka et al, 2017 ), PD ( Ding et al, 2016 ; Dong et al, 2016 ; Ma et al, 2016 ), and ALS ( Freischmidt et al, 2013 ), emerge as prion-specific biomarker candidates. Other prion infected exosomal miRNAs with diagnostic potential include let-7b-5p, miR-29b-3p, miR-222-3p, and miR-342-3p; these miRNAs display inverse deregulation in prion infected exosomes (upregulation, Bellingham et al, 2012 ) compared to ALS (let-7b-5p in ALS patients serum, Freischmidt et al, 2013 ), or AD [miR-29b-ep in AD patients serum ( Geekiyanage et al, 2012 ) and/or PBMCs ( Villa et al, 2013 ), miR-222-3p in AD patients serum ( Zeng et al, 2017 ) and miR-342-3p in AD serum ( Tan et al, 2014 )]. Other upregulated in prion infected exosomes miRNAs, such as let-7i-5p and miR-128-3p, and the downregulated miR-146a-5p, display similar deregulation patterns in MS patients exosomes (let-7i-5p, Kimura et al, 2018 ), Primary Progressive (PPMS) MS patients serum (miR-128-3p, Vistbakka et al, 2017 ) and AD (miR-146a-5p, Kiko et al, 2013 ; Dong et al, 2015 ) or PD patients serum (miR-146a-5p, Ma et al, 2016 ).…”
Section: Altered Mirnas As Potential Diagnostic Tools In Prion Diseasmentioning
confidence: 99%
“…MiR-483-5p and miR-106b target MAPT and FYN for tau protein synthesis and phosphorylation, respectively [ 69 , 165 ]. For neuronal function, miR-222 targets CDKN1B to influence cell cycle and apoptosis [ 68 ]; miR-191 targets TMOD2 and REST to regulate axonal guidance and dendritic growth [ 166 ]; and both miR-486-5p and miR-502-3p are the regulators of dynactin for neuronal function [ 69 ]. The potential mechanisms of miR-126-5p, miR-148-5p, and let-7d in AD are not well known.…”
Section: Discussionmentioning
confidence: 99%
“…miR-574-5p mPGES-1 competitively regulates genes related to inflammation and proliferation [169] is increased in the cortex of APP KO mice [171] miR-206 MyoD competitively regulates genes related to differentiation [170] is increased in the brain of an AD mouse model [172] miR-222 CDK4 cooperatively regulates cellular senescence by targeting genes related to the cell cycle [174] is decreased in the serum of AD patients [173] miR-122 BCKDK, ALDOA, NDRG3, CCNG1, CAT1 enhances destabilization of miRNA in the regulation of energy metabolism, stress response and cell cycle [176] is increased in the brain of AD patients [175] FMRP miR-128-3p mGluR5 competitively regulates astroglial development by targeting glutamate receptor genes [179] is increased in monocytes of AD patients [178] miR-181d MAP1B, Calm1 cooperatively regulates axon elongation by targeting genes crucial for calcium signaling [180] is altered in an AD model and in AD patients [181] miR-125b NR2A cooperatively regulates synaptic strength by targeting an NMDA receptor subunit gene [182] is increased in the CSF of AD patients [183] miR-132 p250GAP? cooperatively regulates synaptic strength possibly by targeting genes related to Rho family GTPase [182] is decreased in the exosome of AD patients [184] hnRNP C miR-544 SOCS1 competitively regulates circRNA in inflammation by targeting genes related to cytokine signaling [185] is increased in high LOAD risk SNPs [186] RCAN1 [190] is decreased in the serum of AD patients [192] miR-18b is increased in serum of AD patients [192] miR-351 UVRAG negatively regulates miRNA biogenesis in autophagy by targeting genes related to the autolysosomal pathway [190] is increased in the hippocampus of an AD mouse model [193] miR-125a is increased in AD cellular model [194] PABP miR-2 n.d. facilitates miRISC onto the 3'-UTR of targeting gene [114] n.d.…”
Section: Celf1mentioning
confidence: 99%
“…Both miR-574-5p and miR-206 were found to be dysregulated in AD patients [ 171 , 172 ]. In addition, CELF1 jointly acts as a modulator of translation with miR-222, a significantly lowered miRNA in the blood of AD patients [ 173 , 174 ], and enhances the deadenylation and degradation of miR-122, an upregulated miRNA in the brain with AD patients [ 175 , 176 ]. FMRP and hnRNP C oppositely regulate Amyloid precursor protein (APP) translation in the hippocampus of an AD animal model, and their dysregulation was observed in the hippocampus synaptosomes of patients with sporadic AD [ 177 ].…”
Section: Interplay Between Rna-binding Proteins and Micrornas In Neurodegenerative Diseasementioning
confidence: 99%